2010
DOI: 10.1155/2010/525034
|View full text |Cite
|
Sign up to set email alerts
|

The Vacuolar-TypeH+-ATPase in Ovine Rumen Epithelium is Regulated by Metabolic Signals

Abstract: In this study, the effect of metabolic inhibition (MI) by glucose substitution with 2-deoxyglucose (2-DOG) and/or application of antimycin A on ovine rumen epithelial cells (REC) vacuolar-type H+-ATPase (vH+-ATPase) activity was investigated. Using fluorescent spectroscopy, basal pHi of REC was measured to be 7.3 ± 0.1 in HCO3−-free, glucose-containing NaCl medium. MI induced a strong pHi reduction (−0.44 ± 0.04 pH units) with a more pronounced effect of 2-DOG compared to antimycin A (−0.30 ± 0.03 versus −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Thus, in yeast, it was early shown that vacuolar V-ATPases rapidly disassemble upon glucose deprivation and they reassemble when the sugar is added back to the growth medium [37]. This same behaviour has been observed in renal epithelial cells [38,39] and, probably, it plays a role in other tissues, as suggested by results on ovine rumen [40]. The first indication of a regulatory link between carbohydrate metabolism and reversible assembly of the H + -pump came from osteoclasts and kidney cells, where aldolase was identified as an interacting partner with subunit E that influenced the assembly of the holoenzyme [41].…”
Section: Structure Of V-atpasesmentioning
confidence: 58%
“…Thus, in yeast, it was early shown that vacuolar V-ATPases rapidly disassemble upon glucose deprivation and they reassemble when the sugar is added back to the growth medium [37]. This same behaviour has been observed in renal epithelial cells [38,39] and, probably, it plays a role in other tissues, as suggested by results on ovine rumen [40]. The first indication of a regulatory link between carbohydrate metabolism and reversible assembly of the H + -pump came from osteoclasts and kidney cells, where aldolase was identified as an interacting partner with subunit E that influenced the assembly of the holoenzyme [41].…”
Section: Structure Of V-atpasesmentioning
confidence: 58%
“…Moreover, an antiapoptotic function for the B subunit of vH ϩ -ATPase has been proposed by various groups (16,29). In our previous study (28), the expression of the regulative vH ϩ -ATPase B subunit protein was drastically reduced or absent in rumen epithelium protein extracts from sheep with prolonged energy deficiency. Here, when compared with h-fed sheep, we found a higher total number of vH ϩ -ATPase B subunit expressing cells and, in F3-5 REC populations, also a higher amount of vH ϩ -ATPase B subunit protein, which could mean a lower rate of apoptosis.…”
Section: Discussionmentioning
confidence: 74%
“…As in our previous experiments (28), the effect of substrate and/or energy deficiency has been investigated, the aim of the present study has been to explore a putative role of the vH ϩ -ATPase in the functional adaptation of the rumen epithelium to a concentrate-supplemented diet. To this purpose, sheep were fed either an ad libitum hay diet (h diet) or a diet consisting of hay ad libitum and additional concentrate (h/c diet).…”
mentioning
confidence: 99%
See 2 more Smart Citations